2012
DOI: 10.1007/s00442-012-2266-3
|View full text |Cite
|
Sign up to set email alerts
|

Mean residence time of leaf number, area, mass, and nitrogen in canopy photosynthesis

Abstract: Mean residence time (MRT) of plant nitrogen (N), which is an indicator of the expected length of time N newly taken up is retained before being lost, is an important component in plant nitrogen use. Here we extend the concept MRT to cover such variables as leaf number, leaf area, leaf dry mass, and nitrogen in the canopy. MRT was calculated from leaf duration (i.e., time integral of standing amount) divided by the total production of leaf variables. We determined MRT in a Xanthium canadense stand established w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…An increase in the LAI was reported in response to the N fertilizer application thereby suggesting an increase in the yield of the rice plants. Similarly, high LAI in response to high N application has been reported by Hirose and Oikawa (2012). In present investigation, total chlorophyll content was found to be higher in response to all the treatments of N, which was found in accordance with Li et al (2012) who showed that in rice seedlings chlorophyll content decreased by 8% when fed with low N and increased by 12% when fed with high N. Very close link between chlorophyll and N content has been proved earlier by Amaliotis et al (2004).…”
Section: Discussionsupporting
confidence: 90%
“…An increase in the LAI was reported in response to the N fertilizer application thereby suggesting an increase in the yield of the rice plants. Similarly, high LAI in response to high N application has been reported by Hirose and Oikawa (2012). In present investigation, total chlorophyll content was found to be higher in response to all the treatments of N, which was found in accordance with Li et al (2012) who showed that in rice seedlings chlorophyll content decreased by 8% when fed with low N and increased by 12% when fed with high N. Very close link between chlorophyll and N content has been proved earlier by Amaliotis et al (2004).…”
Section: Discussionsupporting
confidence: 90%
“…The concept of MRT ( Hirose, 2011 , 2012 ) was employed for the analysis of leaf dynamics. Definition and calculation for MRT and related variables of leaf number, area, mass and N followed Hirose and Oikawa (2012) . First, leaf duration (LD i , [i]d) in the period [0, T ] is calculated: where f i ( t ) and g i ( t ) are the leaf production and loss at time t , respectively, both accumulated from the date of transplanting ( t = 0) when no true leaf emerged.…”
Section: Methodsmentioning
confidence: 99%
“… Hirose and Oikawa (2012) demonstrated that mean residence time (MRT, d) defined for leaf number, area, dry mass and N (collectively ‘leaf variables’) was useful for the study of leaf dynamics. The concept of MRT was introduced earlier as one of the two factors comprising plant N use efficiency (NUE, g g −1 N; Berendse and Aerts, 1987 ) and defined as the expected length of time plant N is retained in the plant body before being lost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total nitrogen concentration in soil has traditionally been reported as the main factor in biomass accumulation because it increases photosynthesis as a large fraction of the leaf nitrogen is invested in the photosynthetic apparatus and leaf nitrogen contents reflect the amounts of photosynthetic proteins [10] [11]. In general, the growth of plants at higher irradiance and nitrogen availabilities includes a higher net photosynthesis and nitrogen leaf concentration [12].…”
Section: Introductionmentioning
confidence: 99%